Scientific mobility: An analysis of Germany, Austria, France and Great Britain - Sonia Conchi; Carolin Michels (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2014)
[Introduction ...] The structure of this report is as follows. It starts with a brief review of the literature on international research collaboration, scientific mobility and return migration and a brief introduction to German migration behavior. The introduction to the topic is followed by a description of the data (bibliometric data and data from online survey) and methods used in this report. A bibliometric data set of all German scientists was created to track their movements for a period of 10 years. In a second step, an online survey of German scientists was conducted that will be presented in chapter 3. It also contains a section on data validation in which the second research question is analyzed. The data from the online-survey was used to determine whether the scientists identified in the Scopus database are indeed German scientists and whether their travel behavior is consistent with the Scopus data. The fourth chapter presents the research results regarding scientific mobility in Germany. As a focus of this study is on German scientists' movements, this is the most extensive analysis. It contains a country analysis and in particular analyzes which proportion of German scientists migrates and returns within 10 years. The same data analysis based on Scopus was conducted for the countries Austria, France and Great Britain. The results are compared to Germany to discover patterns of scientific mobility. Additionally a Scopus analysis of co-publications shows differences between scientists with international and national experience. A regression analysis shows effects on the amount of publications and citation rates of scientists with national or international experience. The results of the online survey provide additional information about reasons and motivations for staying abroad and networking through scientific mobility. Finally the research results are discussed in the concluding section.
Keywords: 330